SAT0391 Cumulative Incidence and Clinical Meaning of Severe Infection in a Large Spanish Cohort of Systemic Lupus Erythematosus. (9th June 2015) - Rúa-Figueroa, I.; Pego-Reigosa, J.; Lόpez-Longo, F.; Galindo, M.; Calvo-Alén, J.; Del Campo, V.; Fernández-Nebro, A.; Olivé, A.; Erausquin, C.; Horcada, L.; Uriarte, E.; Tomero, E.; et al.
Abstract : Background: There are scanty data about infection in Systemic Lupus Erythematosus (SLE) patients from large multicenter cohorts. Objectives: To describe the prevalence of severe infection (SInf), investigate associated factors and clinical meaning in a large SLE cohort from Spanish Rheumatology Society Lupus Registry (RELESSER). Methods: Patients with Sinf were compared with patients without SInf in terms of severity, damage, comorbidities and demographic characteristics (bivariate analysis and Cox regression to survival until the first infection). Results: A total of 3.658 SLE patients included, 90% female, median age 32.9 years (DQ 9.7), 93% Caucasian and 5% Hispanic (Amerindian, mestizo). Mean follow-up (months) was 120.2 (SD: ±87.6). A total of 705 (19.3%) of the patients suffered ≥1 SInf, with an overall of 1.227 SInf. The density of incidence was 29.2 (95%CI: 27.6 - 30.9) infections/ 1000 patients-year. The survival until second infection was lower than survival until first infection (log rank p<0.000). There was predominance of bacterial cause (51.9%), with a 30.4% of unknown cause, and the respiratory tract was the most frequent localization 35.5%. A total of 208 (5.7%) patients died during the follow-up period, 24.5% of them by infection. The predominant localization for the fatal infection was the circulatory stream (bacteraemia/sepsis) (42.0%). In the Cox proportional-hazards regression model age at diagnosis (HR 1.016; 95%CI: 1.009-1.023, p=0.0000) Hispanic ethnic (HR 2.151; 95%CI: 1.539-3.005 p=0.0000) corticosteroids (≥10 mg/day) (HR 1.271; 95%CI: 1.034-1.561, p=0.0224) immunosuppressors (HR 1.348; 95%CI: 1.079-1.684 p=0.0085), hospitalization by SLE (HR 2.567; 95%CI: 1.905-3.459, p=0.0000) renal involvement (HR 1.370; 95%CI: 1.130-1.660, p=0.0013), severity Katz index (SKI) (HR 1.160; 95%CI: 1.105-1.217, p=0.0000), damage index (SDI) (HR 1.069; 95%CI: 1.031-1.108, p=0.0003) and tobacco (HR: 1.332; 95%CI: 1.121-1.583, p=0.0011) were all associated with SInf. Time on antimalarials (months) proved to be protective (HR: 0.998; 95%CI: 0.997-0.999, p=0.0022) Conclusions: SInf remains a frequent and potentially fatal complication of SLE and/or immunosuppressive therapies, and it's a marker of more severe disease. Respiratory bacterial infections are the most common SInf in SLE, but bloodstream infections are the most common mortal ones. A previous infectious event seems to increment the risk of a subsequent infection in SLE. SInf are more common in male and Hispanics and is associated age, tobacco use and other co-morbidities. Antimalarials use exerts a time-dependent protective effect Disclosure of Interest: None declared